Validation of in vitro glycaemic index (eGI) and glycaemic load (eGL) based on selected baked products, beverages, and canned foods - Sulung, Nur Khuraishah; Mohd Aziss, Nur ‘Aqilah Salehah; Kutbi, Nur Farhana; Ahadaali, Anisa Amirah; Zairi, Nur Amira; Mahmod, Ilya Iryani; Abu Bakar Sajak, Azliana; Sultana, Sharmin; Azlan, Azrina (Elsevier BV, 2023)
Glycaemic index (GI) is an important characteristic of any newly formulated foods. This study aimed to validate the estimated glycemic index (eGI) and glycaemic load (eGL) of some selected baked products, beverages, and canned foods. Also, further aimed to develop the relationship between eGI and the eGL value. For the method validation, 30 food products were selected. The eGI were determined and compared with published GI values from International GI Table 2021. This study used the in vitro digestion method to determine the eGI and eGL. In the results, it has been observed that baked products showed significant positive correlations (p<0.01) between eGI and eGL. However, an inverse correlation between eGI and fat content (p<0.01) was found for baked products. Instant cocoa A (3 in 1) (51.61 %) showed the highest rate of starch hydrolysis. The fine wholemeal bread (74.54 ± 0.72) yielded the highest eGI value, while the lowest eGI was found in full cream milk (39.95 ± 0.02). However, no correlation was observed between eGI and total available carbohydrates for all samples. Findings of this study suggested that the in vitro method can be used as a preliminary assessment on estimating GI and GL values for selected food samples.